ATTRACTING FOREIGN DIRECT INVESTMENTS IN FIXED CAPITAL (World Conference on Social Sciences, Law and Public Policy, 2026)
Foreign direct investment (FDI) in fixed capital is one of the most important drivers of economic growth, technological advancement, and industrial development. Fixed capital investments include expenditures on long-term assets such as machinery, equipment, buildings, and infrastructure that are essential for expanding production capacity and improving competitiveness. Attracting FDI in this area allows countries to benefit not only from financial resources but also from modern technologies, management expertise, and access to international markets.